Acinar Cell Carcinoma of the Pancreas: A Possible Role of S-1 as Chemotherapy for Acinar Cell Carcinoma. A Case Report - Yamamoto, Tameyoshi; Ohzato, Hiroki; Fukunaga, Mutumi; Imamura, Hiroshi; Furukawa, Hiroshi (JOP. Journal of the Pancreas, 2012)
<!--[if gte mso 9]> Normal 0 14 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> <span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "MS Mincho"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">Context<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "MS Mincho"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US"> Acinar cell carcinoma of the pancreas is a rare malignancy, accounting for 1-2% of pancreatic exocrine malignancies. This rarity makes it difficult to standardize a protocol of treatment for acinar cell carcinoma. Case report A 71-year-old male without any particular past history was referred to our institute with abdominal distention and mild liver dysfunction. Computed tomography (CT) revealed a cystic lesion with a diameter of 3.5 cm, which originated from the neck of pancreas and had solid nodules inside. Several nodules were demonstrated surrounding the cystic tumor. Laparotomy and histological study demonstrated peritoneal dissemination of acinar cell carcinoma. The patient was treated with S-1 monotherapy (80 mg/m2 for four weeks with a two-week interval as one cycle). After one cycle of S-1 monotherapy, CT demonstrated remarkable shrinkage of the main tumor and disappearance of the nodules on the peritoneum. The patient underwent a radical distal pancreatectomy. The patient was then treated with 16 cycles of S-1 monotherapy after the radical pancreatectomy and remains without any recurrence of the disease two years later. Conclusion Initially inoperable acinar cell carcinoma was treated by monotherapy using S-1, resulting in curative operation and two years disease free survival post operation. S-1 might be more effective on acinar cell carcinoma, rather than gemcitabine.